Influence of Quality, Price, Place, and Promotion on Coffee Purchases: Pengaruh Kualitas, Harga, Tempat, dan Promosi terhadap Pembelian Kopi - Ica, Zulfatul Izzah; Sari, Herlinda Maya Kumala (Indonesian Journal of Law and Economics Review, 2024)
This study investigates how product quality, price, place, and promotion influence consumer purchasing decisions for Fore Coffee in Buduran District. Using quantitative methods and a Probability Sampling approach with 96 respondents, data were collected via online questionnaires distributed through social media. Analysis using SPSS version 22 includes validity, reliability, and classical assumption tests, along with multiple linear regression analysis. Results confirm that higher product quality, competitive pricing, accessible locations, and effective promotions significantly impact consumer decisions. The findings suggest that Fore Coffee should prioritize maintaining high product standards, competitive pricing, convenient locations, and engaging promotional strategies to enhance consumer purchasing behavior in Buduran District, offering practical implications for marketing management strategies in the coffee industry. Highlights: Quantitative analysis: SPSS used for robust consumer behavior insights. Marketing influence: Product quality, price, place, promotion impact purchasing decisions. Recommendations: Enhance quality, pricing, and promotions for consumer engagement strategies. Keywords: Coffee industry, consumer behavior, marketing strategies, quantitative research, Fore Coffee.